Energy Efficiency of Polish Farms Following EU Accession (2004–2021) - Adam Wąs; Julia Tsybulska; Piotr Sulewski; Vitaliy Krupin; Grzegorz Rawa; Iryna Skorokhod (Energies)
Modern agriculture requires substantial energy inputs, a significant portion of which are derived from fossil fuels. In the interests of addressing global challenges, such as sustainable resource management and reducing greenhouse gas emissions, this study examines changes in energy efficiency within Polish agriculture following the country’s accession to the European Union. It emphasizes the impact of dynamic structural transformations on energy consumption patterns in the agricultural sector. The research, based on data from Statistics Poland and FADN (Farm Accountancy Data Network) covering the period 2004–2021, analyzes various farm types and their economic sizes. Key indicators include energy intensity in agricultural production, expressed as the ratio of energy consumption to production value, and the share of different energy carriers in total energy inputs. The results demonstrate an overall improvement in energy efficiency during the analyzed period, with energy intensity decreasing by an average of 40%. The most significant improvements were observed in large-scale farms. Additionally, there was a notable decline in the use of solid fuels, offset by increased reliance on diesel fuel and electricity. Despite these positive trends, challenges persist. Energy costs per unit of production value in Poland remain relatively high compared to other EU countries, driven by rapidly rising energy prices and the structure of Polish agriculture, which predominantly produces goods with relatively low added value. Furthermore, variations in energy consumption structures across production types highlight the importance of specialization in enhancing energy efficiency at the farm level.